Coordinating Public Debt and Monetary Management. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
Edited by V. Sundararajan, Peter Dattels, and Hans Blommestein, this volume outlines strategies for managing public debt, developing government securities markets, and coordinating those activities with monetary management through legal, administrative, and operational arrangements. Both transition and market economies are surveyed. The analysis draws partly on the literature on the microstructure of markets and auction systems and on selected country experiences.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet